Perfil químico e atividade Leishmanicida de extratos de fungos endofíticos isolados de Aspidosperma excelsum Benth. - LUZ, Layana Agnes Souza da (2019)
The tropical climate in the Brazilian Amazon provides the proliferation of a variety of microorganisms, including endophytic fungi. The acquisition of myco-therapeutics from the extracts of endophytic fungi is a useful, versatile and renewable source of substances potentially useful to mankind, and may be of great importance to combat neglected diseases such as leishmaniasis. Leishmaniasis is a tropical disease caused by protozoa of the genus Leishmania. These infect around 12 million people in 80 countries around the world and it is estimated that there are 3 million new cases per year. The drug treatments available for leishmaniasis are based on pentavalent antimonial medicines, such as Pentostan® and Glucantime®, which are toxic and not always effective. Thus, the present work had as objective to evaluate the chemical profile of fungi extracts isolated from the plant Aspidosperma excelsum, species of the genus Aspidosperma that has as important characteristic production of indole alkaloids, mostly monoterpenes, which have a variety of biological activities, among them leishmanicidal activity. Initially, 26 fungi of the plant matrix were isolated, after analyzing the chemical profile by high performance liquid chromatography, 6 (with the following codes, AEC 02, AEC 08, AEC 09, AEC 11, AEC 12, AEC 14) were selected that presented in their spectra of ultraviolet spectral pattern similar to the one of indole alkaloids. The leishmanicide assays were performed in vitro with the Leishmania promastigote forms of Amazons, being the estracts tat presented better results with code AEC 11 and AEC 12 with CI-50 = 6.539 μg / mL and CI-50 = 6.539, respectively.